Pacific Pumas in Indian Jungle: Place of Latin America in Indo-Pacific - T. A. Vorotnikova (Vestnik MGIMO-Universiteta)
The article examines the political potential of Latin American countries in bolstering their influence within the Indo-Pacific region (IP). It delves into the Indo-Pacific concept, championed internationally by India and Japan, as an alternative viewpoint in contrast to the predominant orientation towards China as the regional leader in the Asia-Pacific region. Carlos Exudé's "Peripheral Realism" provides the theoretical framework for the study, although Latin American states strive to move beyond their peripheral status.The focus is on four Pacific coastal countries in Latin America: Colombia, Mexico, Peru, and Chile. It identifies key areas of cooperation between these nations and major players in the IP such as India, Japan, South Korea, and Australia. Chile and Peru have established a more robust transpacific partnership compared to their neighbors. However, Mexico possesses a significant advantage due to its unique geographical position intersecting the Atlantic and Pacific routes.Colombia, along with Mexico, Chile, and Peru, formed the Pacific Alliance, an integration association that emphasizes closer ties with Asian countries. Over its decade-long existence, this Alliance has significantly increased in both economic and political significance. The article highlights the pivotal role of this alliance in fostering Asian-Latin American trade and entrepreneurship.The study also delves into the prospects of integrating the two regions by extending the reach of Pacific economic megablocks (Regional Comprehensive Economic Partnership, Trans-Pacific Partnership) to Latin America. After the ratification of the TPP by Mexico, Peru, and Chile, an agreement that unites all four Pacific Ocean continents for the first time emerged. The advent of the RCEP, which includes powerful economies such as China, South Korea, and Japan, demonstrates a clear global shift from the Atlantic to the Pacific and from West to East. The inclusion of Latin American countries in these processes is poised to advance their regional and global interests on the international stage.